KETIMPANGAN PENDIDIKAN DI INDONESIA - Astuti Rahayu (Jurnal Ekonomi & Studi Pembangunan, 2005)
Equal access to education is among the basic human rights and a component of wellbeing. This paper investigates the education in equality in Indonesia by computing Education Gini Index, affecting factor such as gender gap, and its impacts on the provincial per capita income as measured by provincial gross regional domestic product (GRDP) per capita. In addition, the Klassen Typology for Education and GRDP across provinces in the country are also presented.Both direct and indirect methods are utilized to calculate the Index, generating a quinquennial (every 5 year,) dataset on education Gini for population aged above 10, for 26 provinces from 1975 to 2000. At least six findings are generated in this study. First, educational inequality for most of the provinces has been declining during tile periods, with Irian Jaya as an exception. Second, education inequality as measured by the Education Gini Index has inverse association with the average years of schooling. This consequently implies the third that provinces with the higher level of education attainment are most likely to achieve education equality better than those with the lower level. Fourth, gender has no significant relationship with education inequality. Fifth, the incremental per capita provincial GRDP is negatively associated with education inequality. Sixth, seven provinces have been pushing the growth of education equality and thus their GRDP from “bad” to “ideal” condition in Klassen Typology.